Protective factors for depressive symptoms in emerging adulthood. Issue 2 (14th January 2020) - Germani, Alessandro; Delvecchio, Elisa; Li, Jian‐Bin; Mazzeschi, Claudia
Abstract : Emerging adulthood is characterized by pervasive changes in identity and relationships. These challenges can entail problems for subjective well‐being, leading to depressive symptoms. The development of an autonomous‐related self is considered crucial for emerging adults' personal growth and psychological well‐being. Autonomous‐related self is linked to self‐esteem and secure attachment style, which are also protective factors for depression. The current research sought to investigate the relation between autonomous‐related self and depressive symptoms, as well as the role of secure attachment style and self‐esteem, in a sample of 356 Italian emerging adults. Gender differences were taken into account in preliminary analyses. Gender differences emerged for autonomous‐related self and self‐esteem, while secure attachment and depression levels were similar across gender. Our results suggest that autonomous‐related self, mediated by self‐esteem and secure attachment style, is a protective factor for emotional states of depression, controlling for social desirability. These findings emphasize the importance of taking autonomy and relatedness into account in emerging adulthood and represent a starting point for future studies.